The importance of transmission electron microscopy analysis of spermatozoa: Diagnostic applications and basic research. (3rd May 2016) - Moretti, Elena; Sutera, Gaetano; Collodel, Giulia
ABSTRACT: This review is aimed at discussing the role of ultrastructural studies on human spermatozoa and evaluating transmission electron microscopy as a diagnostic tool that can complete andrology protocols. It is clear that morphological sperm defects may explain decreased fertilizing potential and acquire particular value in the field of male infertility. Electron microscopy is the best method to identify systematic or monomorphic and non-systematic or polymorphic sperm defects. The systematic defects are characterized by a particular anomaly that affects the vast majority of spermatozoa in a semen sample, whereas a heterogeneous combination of head and tail defects found in variable percentages are typically non-systematic or polymorphic sperm defects. A correct diagnosis of these specific sperm alterations is important for choosing the male infertility's therapy and for deciding to turn to assisted reproduction techniques. Transmission electron microscopy (TEM) also represents a valuable method to explore the in vitro effects of different compounds (for example drugs with potential spermicidal activity) on the morphology of human spermatozoa. Finally, TEM used in combination with immunohistochemical techniques, integrates structural and functional aspects that provide a wide horizon in the understanding of sperm physiology and pathology.Abbreviations: transmission electron microscopy: TEM; World Health Organization: WHO; light microscopy: LM; motile sperm organelle morphology examination: MSOME; intracytoplasmic morphologically selected sperm injection: IMSI; intracytoplasmic sperm injection: ICSI; dysplasia of fibrous sheath: DFS; primary ciliary dyskinesia: PCD; outer dense fibers: ODF; assisted reproduction technologies: ART; scanning electron microscopy: SEM; polyvinylpirrolidone: PVP; tert-butylhydroperoxide: TBHP